2008
DOI: 10.1016/j.schres.2007.12.487
|View full text |Cite
|
Sign up to set email alerts
|

Change in metabolic syndrome parameters with antipsychotic treatment in the CATIE Schizophrenia Trial: Prospective data from phase 1

Abstract: Background-The metabolic syndrome (MS) is associated with increased risk for diabetes mellitus and coronary heart disease, and is highly prevalent among schizophrenia patients. Given concerns over antipsychotic metabolic effects, this analysis explored MS status and outcomes in phase 1 of the CATIE Schizophrenia Trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
151
3
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(167 citation statements)
references
References 49 publications
10
151
3
3
Order By: Relevance
“…Despite their widespread use, second-generation antipsychotics (SGAs), especially olanzapine and clozapine, have been associated with metabolic syndrome and the development of type 2 diabetes (Cohen and Correll, 2009;Meyer and Stahl, 2009;Yood et al, 2009). However, the risk of metabolic complications differs within the class of first-generation antipsychotics (FGAs) and SGAs, with high-potency FGAs and more recent SGAs, such as aripiprazole and ziprasidone, having smaller metabolic burden compared with the rest of the antipsychotic drugs (Meyer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Despite their widespread use, second-generation antipsychotics (SGAs), especially olanzapine and clozapine, have been associated with metabolic syndrome and the development of type 2 diabetes (Cohen and Correll, 2009;Meyer and Stahl, 2009;Yood et al, 2009). However, the risk of metabolic complications differs within the class of first-generation antipsychotics (FGAs) and SGAs, with high-potency FGAs and more recent SGAs, such as aripiprazole and ziprasidone, having smaller metabolic burden compared with the rest of the antipsychotic drugs (Meyer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between metabolic problems, such as obesity, diabetes and elevated lipids, and the expression of Apo has been frequently investigated in the general population (Padrao, Ferreira, Vitorino, & Amado, 2012;Ramachandran et al, 2012;Sadler et al, 2012). Due to antipsychotic medications in SZ and mood stabilisers in BD, those patients have an increased risk for metabolic disturbances and altered lipid metabolism (Gibbons, Thomas, Scarr, & Dean, 2010), ultimately contributing to an increased risk for cardiovascular disease (Meyer et al, 2008). Several authors observed an association between Apo concentrations in patients receiving psychiatric medication (e.g., phenothiazines, olanzapine, risperidone) (Dean et al, 2008;Sasaki et al, 1985;Smith, Segman, Golcer-Dubner, Pavlov, & Lerer, 2008;Song et al, 2014).…”
Section: Strength and Limitationsmentioning
confidence: 99%
“…Atypical antipsychotics are also associated with metabolic disorders, and vary in their propensity to cause these adverse effects [6]. In this regard, clozapine and olanzapine have the greatest liability, followed by quetiapine, risperidone, paliperidone, aripiprazole, and ziprasidone, according to the large automated database study [7] and the Clinical Antipsychotic Trials of Intervention Effectiveness study [8]. Recent studies have suggested weightindependent effects of certain atypical antipsychotics such as olanzapine or clozapine on insulin resistance that are above and beyond obesity [9,10].…”
Section: Troductiomentioning
confidence: 99%